The soul of discipline : the simplicity parenting approach to warm, firm, and calm guidance--from toddlers to teens - Payne, Kim John (Ballantine Books, 2015)
"In this groundbreaking book, parenting expert and acclaimed author of the bestselling book Simplicity Parenting Kim John Payne, M.Ed., flips the script on children's challenging or defiant behavior and lays out an elegantly simple plan to support parents in establishing loving, age-sensitive boundaries that help children feel safe and settled. In short: What looks like misbehavior is actually your children's signal that they're feeling lost, that they are trying to find direction and looking to you to guide them back on course. Payne gives parents heartwarming help and encouragement by combining astute observations with sensitive and often funny stories from his long career as a parent educator and a school and family counselor. In accessible language, he explains the relevance of current brain- and child-development studies to day-to-day parenting. Breaking the continuum of childhood into three stages, Payne says that parents need to play three different roles, each corresponding to one of those stages, to help steer children through their emotional growth and inevitable challenging times: The Governor, who is comfortably and firmly in charge--setting limits and making decisions for the early years up to around the age of eight The Gardener, who watches for emotional growth and makes decisions based on careful listening, assisting tweens in making plans that take the whole family's needs into account The Guide, who is both a sounding board and moral compass for emerging adults, helping teens build a sense of their life's direction as a way to influence healthy decision making Practical and rooted in common sense, The Soul of Discipline gives parents permission to be warm and nurturing but also calm and firm (not overreactive). It gives clear, doable strategies to get things back on track for parents who sense that their children's behavior has fallen into a troubling pattern. And best of all, it provides healthy direction to the entire family so parents can spend less time and energy on outmoded, punitive discipline and more on connecting with and enjoying their kids. Praise for Kim John Payne's Simplicity Parenting "[Payne is] like a master closet reorganizer for the soul."--Time "If you are raising children in these anxious times, you need this book. It will inspire you, reassure you, and, most important, it will remind you that less is more."--Katrina Kenison, author of The Gift of an Ordinary Day "Including practical strategies for turning down the volume and creating a pace that fosters calmness, mindfulness, reflection, and individuality in children, Simplicity Parenting should be on every parent's (indeed, every person's) reading list."--Kathleen A. Brehony, Ph.D., author of Awakening at Midlife "Brilliant, wise, informative, innovative, entertaining, and urgently needed, this timely book is a godsend for all who love children, and for children themselves. It provides a doable plan for providing the kind of childhood that kids desperately need today!"--Edward M. Hallowell, M.D., author of The Childhood Roots of Adult Happiness"--